PENANAMAN MANGROVE DALAM PERBAIKAN EKOSISTEM DAN LINGKUNGAN HUTAN MANGROVE DI DESA NELAYAN SEBERANG BELAWAN - Aulia Putra Daulay; Sahat Raja Marigo Girsang; Ratna Sari; Ulil Amri Daulay (Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
The mangrove forest in Nelayan Seberang Medan Belawan Village is fully utilized by the community. Currently, the condition of the mangrove forest has been damaged due to excessive encroachment and conversion into fish ponds, which has destroyed the mangrove ecosystem. The objective of this community service activity is to restore the mangrove ecosystem by replanting mangrove species in the mangrove ecosystem, as well as to raise awareness among the Seberang Fishing Village community about the importance of mangrove forests in providing ecological, economic, and social benefits to coastal communities. The methods used in this activity included community participation in restoring the mangrove ecosystem, caring for the mangrove forest ecosystem by conducting continuous monitoring to reduce damage to the mangrove forest, and planting Rhizophora apiculata as a fast-growing species to accelerate the restoration of the mangrove ecosystem. The results of this activity were the restoration of the mangrove ecosystem by planting 500 seedlings in locations that had been cleared due to logging. community participation in planting as a form of preserving the mangrove forest ecosystem for the ecological and economic interests of coastal communities. The community is also expected to maintain the mangrove species that have been planted at these locations and replace dead mangrove species with new seedlings. The conclusion of this activity is that mangrove forest planting aims to improve the condition of mangrove forests in Nelayan Seberang Village that have been damaged and to raise awareness among the community to protect the environment by planting trees, thereby reducing the percentage of erosion and disasters that can damage the Nelayan Seberang Village area.